Potensi Dasar Manusia dalam Al-Quran dan Relevansinya dengan Skill Competence Building - sulisno, sarwadi; Zaid Barzinji (Kopertais Wilayah III Yogyakarta, 2024)
Humans are special beings with many fascinating aspects to study. The essence of humanity is difficult to fully comprehend because it encompasses various dimensions. When one dimension is understood, another unexplored dimension emerges. This writing is motivated by a lack of awareness of human potential from an interpretive perspective, which has caused the direction of skill competence building to deviate from its natural path. Skill competence building, which should be a means of developing human potential, often fails to achieve its goals. One indication of this is the orientation of knowledge in competence building. This research is qualitative with a descriptive-analytical approach to describe and analyze skill competence building based on human potential from the perspective of tafsir maudu’i. The object of this study is humans, who act as both the object and subject of human potential. The results of this study are: 1) Skill building is the realization of human potential to develop and transform divine and human values, equipping students with productive abilities so they can function and develop according to the times. 2) Humans consist of physical, spiritual, and intellectual components; this concept requires a tangible development process, so skill competence building must be based on the concept of the unity of body, spirit, and mind to produce intellectually intelligent and morally commendable Muslims. 3) Humans have varied responses to each other; the task of skill competence building is to understand these differences and develop them according to each individual's response